Cephalic Pancreaticoduodenectomy for Bleeding Duodenal Arteriovenous Malformation - Ortiz, Ruben; Dominguez, Eva; Barrena, S.; Martinez, Leopoldo; Prieto, Gerardo; Burgos, Emilio; Tovar, Juan Antonio (European Journal of Pediatric Surgery Reports, 2014)
Introduction Treatment of recurrent severe gastrointestinal bleeding due to arteriovenous malformations may require complex resections. In some particular locations, extensive surgery is the only way out, as shown in this report.Case Report A 2.5-year-old child suffered repeated episodes of upper gastrointestinal bleeding since the first month of life. After an extensive diagnostic workout, the diagnosis of duodenal arteriovenous malformation was established. Cephalic pancreaticoduodenectomy with pyloric preservation was performed and no further episodes of bleeding occurred in the ensuing 2 years.Conclusion Bleeding malformations located in the pancreaticoduodenal area can be effectively treated in children by pylorus-preserving cephalic pancreaticoduodenectomy.
Keywords: gastrointestinal bleeding; vascular malformation; pancreaticoduodenectomy; arteriovenous malformation